Nghiên cứu lớp phủ bảo vệ chống ăn mòn thân thiện môi trường trên cơ sở epoxy và axit indol-3 butyric - Trúc, Trịnh Anh; Lượng, Bùi Trần; Xuân Hằng, Tô Thị (Vietnam Journal of Chemistry, 2014)
The well documented toxicity and carcinogenicity of corrosion inhibitor pigments based on chromate salts has led to a considerable research effort to identify environmentally acceptable alternatives of equivalent efficiency. In this paper, indole-3 butyric acid (IBA) was used for the improvement of the corrosion performance of an epoxy coating applied on carbon steel. Corrosion resistance of the coated steel was evaluated by electrochemical impedance spectroscopy. It was found that a small quantity (2%) of IBA significantly enhanced the protective properties of the epoxy coating by comparison with the pure epoxy. In addition, the adhesion test showed that IBA also improved the adhesion of the coating to the metal substrate